Experience and lessons learned relating to investigational product supply in the design and delivery of a paediatric investigator-initiated clinical trial - Mandy Wan; Mark A. Turner; Gilles Cambonie; Ruth Kemper; Naouel Bouafia; Lea Levoyer; Alpha Diallo; Mikko Hallman; Jean-Christophe Rozé (Contemporary Clinical Trials Communications)
The management of investigational product (IP) supply is a complex endeavour when designing and delivering clinical trials. In contrast to industry-sponsored trials where IP supplies are coordinated by teams of specialists working together throughout the entire supply chain, investigator initiated clinical trials often face IP-related challenges that can result in substantial trial delays, higher costs, and even early termination of the trial. Despite the challenges faced by investigators, there has been relatively few discussions on this topic in the literature. In this short communication, we describe our experiences and the lessons learned in managing IP supply during the design and execution of a multinational paediatric investigator initiated clinical trial. These experiences are shared to provide researchers with tools and strategies to improve the future implementation of investigator-initiated clinical trials.